116k views
4 votes
Please help me solve this!! I keep overthinking it!!!

Use the distributive property to write the product in standard form.
3(2 − 1)

User Kuncajs
by
5.2k points

2 Answers

2 votes

Answer:

3

Explanation:

3(2-1)=6-3=3

User Skdonthi
by
5.7k points
3 votes

By the distributive property of multiplication over subtraction,

3(2 - 1) = 3(2) - 3(1)

Standard form? I don't know what they're really talking about, let's go with:

Answer: 3(2) - 3(1)

That of course equals 6 - 3 = 3

User Cygnim
by
4.8k points